The Influence of Stress on Front Office Work Motivation at the Four Point Hotel Medan - Purba, Veni Agri Vici; Sitorus, Risda Mora; Ginting, Arnold Brema; Simbolon, Gregorious; Monica Agustina (Jurnal Multidisiplin Sahombu, 2024)
Prolonged work stress can have a negative impact on employee well-being and can reduce the quality of their performance. On the other hand, work motivation is an important factor in improving employee performance. Therefore, it is important to identify the effect of work stress and work motivation on front office performance at the Four Point Hotel Medan. The purpose of this study was to determine the effect of stress on front office work motivation at the Four Point Hotel Medan. The method used was a quantitative research method in the form of a questionnaire with data processing using SPSS 22.0. The results of this study indicate that there is a positive relationship between stress and work motivation. This means that the higher the stress on front office employees, the higher the work motivation. Likewise, the lower the stress on employees, the lower the work motivation.